2018
DOI: 10.1016/j.applanim.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Stranger danger? An investigation into the influence of human-horse bond on stress and behaviour

Abstract: Human-animal bond is receiving increasing attention and is thought to confer benefits on wellbeing and performance in working animals. One important benefit of bonding is the "safe base" an attachment figure provides, which manifests in better coping and increased exploration during potential threat. However, there is limited research exploring the existence or benefits of human-horse bonds, though bonding is sought after by both pleasure and elite riders. The purpose of the current study was to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
(40 reference statements)
1
31
2
Order By: Relevance
“…A shared sense of co-being between horse and rider alongside horse owners describing their equine partners as soul mates commonly defines horse–human relationships [ 22 ], and it is this bond that expedites positive influences on human wellbeing when interacting with a familiar horse [ 23 , 24 , 63 ]. The sudden restriction on access to horses and the green spaces they commonly inhabit, may have not only limited the physical exercise of horse owners, but concurrently contributed to increased levels of anxiety and loneliness at a time when external pressures and quarantine measures related to COVID-19 were likely to already be amplifying these feelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A shared sense of co-being between horse and rider alongside horse owners describing their equine partners as soul mates commonly defines horse–human relationships [ 22 ], and it is this bond that expedites positive influences on human wellbeing when interacting with a familiar horse [ 23 , 24 , 63 ]. The sudden restriction on access to horses and the green spaces they commonly inhabit, may have not only limited the physical exercise of horse owners, but concurrently contributed to increased levels of anxiety and loneliness at a time when external pressures and quarantine measures related to COVID-19 were likely to already be amplifying these feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Horse owners also often extol the beneficial impact of physical contact with their horse and how their relationship with their horse/s promotes positive mental wellbeing and physical health [ 22 , 23 , 24 ]. The rapid implementation of changes to normal equine management practices and equestrian activities associated with the quarantine measures to control the impact of COVID-19 in the UK, therefore, have the potential to affect human and equine welfare, and warrant further investigation to develop strategies to lessen the impact of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs might have learned to associate their owners' positive emotional messages with positive outcomes [19]. In horses, it has been shown that behavior or physiological stress responses did not differ between a familiar or unfamiliar handler, indicating that the human-horse-bond might be less salient in novel, potentially threatening situations compared to the human-dog-bond [69]. Future studies of social referencing paradigms in horses should, therefore, include both a neutral condition as well as familiar and unfamiliar informants.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, Squibb and colleagues [ 29 ] determined that there was no correlation between proactive behaviour and horse HR when the horses were asked to perform stressful tasks (walk over a tarp or through streamers). Further, Ijichi and colleagues [ 13 ] described no differences in the behavioural or physiological responses of horses led by a familiar vs. unfamiliar handler through two novel object tests. Human traits can, therefore, impact horse response, although the casual factors involved in the human–horse interaction are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Physical contact, social interaction, and bonding during EFL can lead to an emotional connection between the adolescent and the horse, facilitating the development of functional relationships in insecure adolescents [ 2 ]. Human–horse interaction includes a whole array of social interactions, including agonistic, affiliative, cooperative, and avoidance behaviours [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Despite the negative connotation of avoidance and aggressive behaviours for horse welfare, the behavioural feedback of therapy horses is a direct reaction to human body language, behaviour, and/or physical attributes during EAT and EFL programs [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%